Natural and synthetic estrogenic compounds in the Pearl River Estuary and northern shelf of the South China Sea - Carina Deich; Marion Kanwischer; Ruifeng Zhang; Joanna J. Waniek (Oceanologia, 2023)
Endocrine disrupting compounds and in particular estrogenic substances have the ability to interact with the hormone system of organisms. Among them are not only synthetic but also natural substances that potentially stress the aquatic ecosystem. High human population densities such as around the Pearl River Estuary (PRE) are suspected of exerting significant anthropogenic pressure onto coastal areas. In this study, natural and synthetic estrogens as well as estrogen-like substances derived from plants and fungi were investigated in the PRE and at the adjacent northern shelf of the South China Sea. Maximum concentration of 3.6 ng L−1 for estrone (E1), 0.7 ng L−1 for 17α-ethinylestradiol (EE2), 12.9 ng L−1 for genistein (GEN), 11.9 ng L−1 for daidzein (DAI) and 1.9 ng L−1 for zearalenone (ZEN) were observed. While E1 and EE2 were detected in fresh and saltwater samples, GEN, DAI and ZEN were observed only at freshwater sampling sites. During the investigations, the analysis of 17β-estradiol (E2) and EE2 indicated a strong matrix dependence. Additionally, an estrogen screen observation showed estrogenic activity in form of estradiol equivalent quotients up to 0.18 ng L−1.